The Coach Leadership Style: How it Impacts on the Sports Commitment and Playing Skills of Student Tennis Athletes? - Setiyo Hartoto; Mochamad Ridwan; Dony Andrijanto; Joesoef Roepajadi; Muhamad Asrul Sidik; Armando Monterrosa-Quintero; Dan Iulian Alexe; Dragos Ioan Tohanean; Edi Setiawan (Physical Education Theory and Methodology, 2023)
Study purpose. The objective of this study was to investigate the effect of the coach’s leadership style model on increasing the level of sports commitment and tennis skills.